A comparative study of C4 and C5 alcohol treated diesel–biodiesel blends in terms of diesel engine performance and exhaust emission. (1st September 2016) - Imdadul, H.K.; Masjuki, H.H.; Kalam, M.A.; Zulkifli, N.W.M.; Alabdulkarem, Abdullah; Kamruzzaman, M.; Rashed, M.M.
Highlights: Pentanol and n -butanol are promising blending component for biodiesel blends. Pentanol showed better overall performance and emission than n -butanol. The BP increased by 4.65–12.77% for alcohol treated biodiesel blends. Alcohol treated biodiesel blends decreased the BSFC by 2.2–10.87%. Alcohols mixed with biodiesel diminished the HC by 50–67.7% and CO by 18.4–33.8%. Abstract: Use of pure alcohols or alcohols blended with petroleum-based fossil fuel or biodiesel blends as engine fuel is an attractive alternative solution for internal combustion engines. This study conducted an experiments in a single cylinder, four-stroke, water-cooled, direct-injection diesel engine. Engine performance and emission characteristics of diesel– Alexandrian laurel biodiesel blends with 15 and 20 vol.% of n -butanol (C4 ) and pentanol (C5 ) as blending components were investigated and compared under different speed conditions. Results show that brake power and brake specific fuel consumption of the engine using C4 and C5 alcohols mixed with biodiesel blends were improved greatly than that using biodiesel. The emissions of hydrocarbon and carbon monoxide were extremely reduced with increasing nitric oxide and carbon dioxide, but carbon dioxide decreased at maximum speed. Finally, it can be conclude that, C5 alcohol is preferred than C4 alcohol because of its elevated performance and emission.